Mucosal-Associated Invariant T Cells Display a Poor Reconstitution and Altered Phenotype after Allogeneic Hematopoietic Stem Cell Transplantation - Solders, Martin; Erkers, Tom; Gorchs, Laia; Poiret, Thomas; Remberger, Mats; Magalhaes, Isabelle; Kaipe, Helen (Frontiers in Immunology, 2017)
Mucosal associated invariant T (MAIT) cells are innate-like T cells which are important in the defense against certain bacteria and yeast. The reconstitution of MAIT cells after allogeneic hematopoietic stem cell transplantation (HSCT) is not known. We investigated MAIT cell phenotype and function in 17 patients devoid of relapse and severe graft-versus-host disease (GvHD) in paired samples collected 1-2, 3-6, 12, and 24 months after transplantation. Data was compared to 17 healthy controls (HC), as well as 22 patients with acute GvHD grade 2-3. The frequency of MAIT cells within CD3+ cells was approximately 10-fold lower than in HC, and did not increase over the two years following HSCT. MAIT cells in HSCT patients displayed an elevated expression of CD69 and intracellular granzyme B, and were predominantly composed of CD4/CD8 double negative cells. The expression of PD-1 on MAIT cells was low and did not change during the observational time, whereas the CD3+CD161dim/negTCRVα7.2dim/neg cells (non-MAIT T cells) displayed a high expression early after HSCT that decreased to normal levels at 24 months. MAIT cells collected 2-6 months post-HSCT showed an impaired IFN-γ and perforin response after bacterial stimulation, but the response was restored at 24 months. Patients with acute GvHD had similar proportions of MAIT cells as patients with grade 0-1, but consisted mainly of CD8+ cells. Lastly, MAIT cells were more sensitive to cyclosporine A and sirolimus than non-MAIT T cells. To conclude, MAIT cell reconstitution following HSCT is deficient compared to non-MAIT T cells and GvHD grade ≥2 is not correlated with MAIT cell frequency. MAIT cell functionality was impaired early after HSCT, but restored at 24 months post-HSCT. MAIT cells have an increased sensibility to common immunosuppressive drugs, which maybe could explain their hampered reconstitution after HSCT.